GDP Growth Consequences for the Air Pollution Levels in Armenia - Ghantarchyan, Ruben; Terzyan, Haroutyun; Gasparyan, Garri («Տնտեսագետ» հրատ․)
Every year scientists, especially economists, pay more and more attention to environmental issues, since their existence and the risks of further aggravation threaten the possibility of sustainable economic development and ensuring public welfare. In general, the most urgent and risky of the environmental issues is the atmospheric air pollution, which is a negative result of the economic activity of the society, which causes the involvement of economic thought in assessing the impact of economic activity on atmospheric emissions. In this work taking into account the best international experience in assessing the impact of economic activity on atmospheric emissions and in order to get an idea of the compliance of the RA economy with the green standards, with the help of econometric models, an assessment of the impact of GDP volumes on atmospheric emissions in Armenia has been carried out. In particular, within the framework of the study using the ARDL model with time series, the dependencies between two key indicators have been studied: the volumes of harmful substances released into the atmosphere and the volumes of GDP in the period from 2000 to 2022, taking into account the impact of global economic crises. As a result, it has been revealed that in the short and long term there is a direct relationship between atmospheric emissions and GDP volumes, in particular, an increase in GDP by 1% in the short term in a given year, all other things being equal, leads to an increase in emissions by an average of 0.2% in a given year, and in the long term, an increase in GDP by 1%, all other things being equal, after 12 years will be accompanied by an increase in emissions by an average of 0.6%, which is quite worrying and is an impetus for the need of greening the RA economy.
Keywords: Atmosphere